Penerapan Video Recitation Learning sebagai Model Pembelajaran di RA Raudlatul Hasan - Wulandari, Putri; Wisudaningsih, Endah Tri; DP, Terza Travelancya (AS-SABIQUN, 2023)
This study aims to find out how to apply Video Recitation Learning as a learning model at RA Raudlatul Hasan and what the benefits of Video Recitation Learning habituation as a learning model at RA Raudlatul Hasan. The method that researchers use is a qualitative approach with the type of case study type of research. The techniques used by researchers un collecting data, namely observation, interviews and documentation. Researchers also used data reduction techniques, data display, and drawing conclusions in analyzing the data. The results in this study are the application of the video recitation learning learning model carried out when learning activities take place after various kinds of habituation are carried out such as reading short letters, asmaul husna, getting to know various kinds of color and get to know the various kinds of school equipment that are around the teacher delivering learning material accompanied by quite creative video media, so that is easier for students to understand, finally the teacher gives several assignments related to learning material through video media. These assignments can be done outside class hours. The teacher giver two days to complete it. After the material and video based assignment are finished, the teacher immediately oractices them and vice versa the students compete to practice them according to the teacher’s directions. Recitation learning is that children tend to be active and creative, create an effective and fun learning atmosphere, can train children’s absorption and can develop children’s imagination.